A SEPALLATA gene is involved in the development and ripening of strawberry (Fragaria×ananassa Duch.) fruit, a non-climacteric tissue* - Seymour, Graham B. (Oxford University Press, 2011)
Climacteric and non-climacteric fruits have traditionally been viewed as representing two distinct programmes of ripening associated with differential respiration and ethylene hormone effects. In climacteric fruits, such as tomato and banana, the ripening process is marked by increased respiration and is induced and co-ordinated by ethylene, while in non-climacteric fruits, such as strawberry and grape, it is controlled by an ethylene-independent process with little change in respiration rate. The two contrasting mechanisms, however, both lead to texture, colour, and flavour changes that probably reflect some common programmes of regulatory control. It has been shown that a SEPALLATA(SEP)4-like gene is necessary for normal ripening in tomato. It has been demonstrated here that silencing a fruit-related SEP1/2-like (FaMADS9) gene in strawberry leads to the inhibition of normal development and ripening in the petal, achene, and receptacle tissues. In addition, analysis of transcriptome profiles reveals pleiotropic effects of FaMADS9 on fruit development and ripening-related gene expression. It is concluded that SEP genes play a central role in the developmental regulation of ripening in both climacteric and non-climacteric fruits. These findings provide important information to extend the molecular control of ripening in a non-climacteric fruit beyond the limited genetic and cultural options currently available.